On the topic of interdisciplinary collaboration between art and music - Duby, Marc; Cooper, Paul (Arts Research Africa, The Wits School of Arts, University of the Witwatersrand, 2020)
This improvised performance drew from a shared body of knowledge in which the aesthetic outcome (as “product”) is considered as of lesser significance than the underlying artistic and creative processes (the real-time “making” aspect) underpinning the venture. This session explored processes of cooperative and circulatory reciprocity in a triangular encounter between musician, artist, and audience.
This improvised performance drew from a shared body of knowledge in which the aesthetic outcome (as “product”) is considered as of lesser significance than the underlying artistic and creative processes (the real-time “making” aspect) underpinning the venture. This session explored processes of cooperative and circulatory reciprocity in a triangular encounter between musician, artist, and audience.
Keywords: artistic research, arts research, decolonisation, arts pedagogy